Gel Polymer Electrolytes Based on Silica-Added Poly(ethylene oxide) Electrospun Membranes for Lithium Batteries - Maria Assunta Navarra (Membranes, 2018)
Solid polymer electrolytes, in the form of membranes, offering high chemical and mechanical stability, while maintaining good ionic conductivity, are envisaged as a possible solution to improve performances and safety in different lithium cell configurations. In this work, we designed and prepared systems formed using innovative nanocomposite polymer membranes, based on high molecular weight poly(ethylene oxide) (PEO) and silica nanopowders, produced by the electrospinning technique. These membranes were subsequently gelled with solutions based on aprotic ionic liquid, carbonate solvents, and lithium salt. The addition of polysulfide species to the electrolyte solution was also considered, in view of potential applications in lithium-sulfur cells. The morphology of the electrospun pristine membranes was evaluated using scanning electron microscopy. Stability and thermal properties of pristine and gelled systems were investigated uisng differential scanning calorimetry and thermal gravimetric analysis. Electrochemical impedance spectroscopy was used to determine the conductivity of both swelling solutions and gelled membranes, allowing insight into the ion transport mechanism within the proposed composite electrolytes.